Curcumin affects β‐catenin pathway in hepatic stellate cell in vitro and in vivo. (19th June 2014) - Cui, Lei; Jia, Xin; Zhou, Qian; Zhai, Xuguang; Zhou, Yajun; Zhu, Huixia
Abstract Objectives Emerging evidence indicates that Wnt/β‐catenin pathway is linked to the fibrosis of different organs including liver fibrosis. β‐Catenin promotes hepatic stellate cells (HSCs) activation, a key event in the development of liver fibrosis, and has emerged as a novel mediator of fibrosis. Curcumin, a natural active ingredient derived from turmeric, possesses an inhibitory effect on liver fibrosis. This study is aimed to examine whether curcumin affects β‐catenin expression/activity in HSCs and explores the underlying mechanisms. Methods The researchers used Western blot, real‐time PCR, transfection assay and electrophoretic mobility shift assay and employed cultured HSCs and rat model of liver injury. Key findings Results showed that curcumin could reduce β‐catenin protein level in HSCs in vitro and in vivo. Both β‐catenin transactivation activity and DNA‐binding activity were suppressed by curcumin. Moreover, nuclear β‐catenin protein level was decreased by curcumin treatment. Further experiments suggested that delta‐like homologue 1 contributed to curcumin inhibition of β‐catenin transactivation activity in cultured HSCs. Conclusions Curcumin affects β‐catenin pathway in HSCs and might suggest a possible new explanation for the effects of curcumin on HSC activation and liver fibrosis.